IMPACT OF CORPORATE GOVERNANCE ON FIRM PERFORMANCE IN SOUTH ASIAN COUNTRIES - BARKAT ULLAH; ZIAULLAH, MUHAMMAD; ATHAR, MUHAMMAD RAZZAQ; FAISAL, MALIK MUHAMMAD; ZULFIQAR, BUSHRA (Bulletin of Business and Economics (BBE), 2022)
This paper investigates the impact of corporate governance on the financial performance of manufacturing firms in South Asian Countries. Financial performance is measured using both accounting and marketing based measures (ROA, ROE and Tobin’s Q). However, corporate governance practices are captured through Board Size, CEO Duality, Audit Quality, Audit Committee Size and Audit Activity. The sample of the study comprised a total of 426 listed manufacturing firms of South Asian Countries for period spans 10 years from 2011 to 2020. Generalized Methods of Moments (GMM) was used for data analysis. We find significant impact of corporate governance on firm performance in the South Asian countries. According to the findings audit committee activity and size, as well as audit quality decisions, should be made efficiently as these factors have great implications for improving the performance of manufacturing firms in the South Asian Countries.